Aktivitas Antipiretik Ekstrak Etanol Buah Belimbing Wuluh (Averrhoa bilimbi) pada Tikus Putih Jantan (ANTIPYRETIC ACTIVITY OF ETHANOL EXTRACT OF BELIMBING WULUH (AVERRHOA BILIMBI) IN MALE WHITE RAT) - Andriyanto, Andriyanto; Isriyanthi, Ni Made Ria; Sastra, Edwin Ligia; Arif, Ridi; Mustika, Aulia Andi; Manalu, Wasmen (Jurnal Veteriner; Vol 18 No 4 (2017)DO - 10.19087/jveteriner.2017.18.4.597, 2018)
The experiment was conducted to study the activity of ethanol extract of belimbing wuluh (EEBW) as antipyretic. Fever induction was done by using difteri pertusis tetanus (DPT) vaccine intramuscularly at a dose of 0.1 mL/100 g BW. Male white rat strain spraque dawley with range of weight by 200 to 300 g was used in this research.Fifteen experimental rats were used to explore the specific time of fever (time of early fever and time of peak fever) which were divided in 2 treatments, i.e. 10 experimental rats with DPT vaccine injection and 5 experimental rats without DPT vaccine injection as control.Fourty experimental rats were used to study effectivity of EEBW as antipyretic which were grouped with factorial randomized design with 4 x 2 and 5 replications. The first factor was various substance administered which consisted of aquadest (control), EEBW 0.88 g/kg BW, EEBW 1.75 g/kg BW, and aspirin 0.004 g/kg BW.The second factor was time of fever detection, i.e. time of early stage fever and time of peak fever. The variable was measured with rectal temperature of the experimental rats by using digital thermometer (correction factor 0.01oC) every 30 minutes. The data were analyzed with t-student dan general linear model (GLM). Increasing of rectal temperature of experimental rats with DPT injection began at 30 minutes post-DPT injection (time of early stage fever) and reached time of peak fever at 210 minutes post-DPT injection. Ethanol extract of belimbing wuluh at dose of 1.75 g/kg BW administered at early fever lowered rectal temperature of the experimental rats compared to the other groups. It was concluded that the administration of EEBW at dose of 1.75 g/kg BW was effective combination in dose and time administration as an antipyretic.